Functional Traits of Fish Species: Adjusting Resolution to Accurately Express Resource Partitioning - da Silva, Victor E. L.; Silva-Firmiano, Luana P. S.; Teresa, Fabrício B.; Batista, Vandick S.; Ladle, Richard J.; Fabré, Nidia N. (Frontiers in Marine Science, 2019)
One of the core challenges of functional diversity is the identification of traits that can accurately be linked to ecological processes. Trait-based metrics have been used to detect and quantify the effects of deterministic processes, such as niche filtering and co-occurrence mechanisms. However, most functional studies have simplified the measured attributes, especially for fish species. Here, we aimed to test the influence of trait resolution and surrogates on the accuracy in expressing resource partitioning among tropical fish species. We assessed pairwise species similarity between distinct ways of express resource use by species (through increasing trait resolution), and tested whether differences in resolutions are strong enough to provide different patterns in the functional structure of tropical fish assemblages. Our study shows that distinct ways of expressing resource partitioning among species may provide different ecological interpretations of this process as different resolutions or surrogates can change pairwise species, similarity.